Diabetics have Inferior Long-Term Survival and Quality of Life after CABG - Järvinen, Otso; Hokkanen, Matti; Huhtala, Heini (International Journal of Angiology, 2019)
A prevalence of diabetes is increasing among the patients undergoing coronary artery bypass grafting (CABG). Data on whether health-related quality of life improves similarly after CABG in diabetics and nondiabetics are limited. We assessed long-term mortality and changes in quality of life (RAND-36 Health Survey) after CABG.Seventy-four of the 508 patients (14.6%) operated on in a single institution had a history of diabetes and were compared with nondiabetics. The RAND-36 Health Survey was used as an indicator of quality of life. Assessments were made preoperatively and repeated 1 and 12 years later.Thirty-day mortality was 2.7 versus 1.6 (p = 0.511) in the diabetics and nondiabetics. One- and 10-year survival rates in the diabetics and nondiabetics were 94.6% versus 97.0% (p = 0.287) and 63.5% versus 81.6% (p < 0.001), respectively. After 1 year, diabetics improved significantly (p < 0.005) in seven, and nondiabetics (p < 0.001) in all eight RAND-36 dimensions. Despite an ongoing decline in quality of life over the 12-year follow-up, an improvement was maintained in four out of eight dimensions among diabetics and in seven dimensions among nondiabetics. Physical and mental component summary scores on the RAND-36 improved significantly (p < 0.001) in both groups after 1 year, and at least slight improvement was maintained during the 12-year follow-up time.Diabetics have inferior long-term survival after CABG as compared with nondiabetics. They gain similar improvement of quality of life in 1 year after surgery, but they have a stronger decline tendency over the years.
Keywords: quality of life; survival; CABG; diabetes mellitus; mortality; angina pectoris; complication